Estudio de mejora en el área de recursos humanos en la empresa “V 13 S.A.C.” - Hurtado Villasis, Caroline Mitchelle (2023)
The objective of this work is to improve the performance of the human resources area of the security company "V13". The area selected was human resources because the core of the business is the service provided by security agents. During the last few years the company has maintained its participation, however, it is looking for growth. First, a brief description of the company will be given, detailing the services it provides and the characteristics of its service. The reasons that justify the development of the research work will be given. Subsequently, the current situation of the company and its environment will be analyzed and a SWOT analysis will be carried out. Next, the processes and indicators will be reviewed. Then the root causes of the improvement opportunities will be identified in order to focus the solutions on the improvement opportunities that will generate a change. After this, the best solutions will be chosen considering the complexity of the solution, the time it will take to implement, the investment required and the impact of the solution on the problem. The development of the solution will be planned and timelines for implementation will be established. Finally, the solutions will be evaluated financially and their viability will be determined, seeking to have a positive benefit-cost indicator.